Pengaruh Media Visual (Gambar) Terhadap Kemampuan Kosakata Anak Autis - Amalia Risqi Puspitaningtyas; Vidya Pratiwi (Al-Aulad: Journal of Islamic Primary Education, 2020)
The barriers possessed by autistic children are communication and language, so that they have lack vocabulary. The purpose of this study is to describe the vocabulary skills of autistic children both before and after the intervention state and analyze the visual media (pictures) on the vocabulary of autistic children.  This research method is quantitative using Single Subject Research (SSR) A-B-A design with A is the baseline and B is an intervention. The results showed there was an influence of the use of visual media (pictures) on the vocabulary ability of autistic children